Assessment Teaching Practice in Civic Education - Gissel Jasbleydy Ariza González; Diego Mauricio Barrera Quiroga (RHS Revista Humanismo y Sociedad)
This article was developed with the purpose of analyzing and understanding the connection between the pedagogical practices and assessment within the process of educating citizens. The study was developed at the Instituto Técnico Agroindustrial de la Amazonia Educational Institution, specifically at the first preschool grade, under the direction of teacher Clara (as we have named her for the purpose of protecting her social identity). During the research, the elements to which the educator gave the greatest importance when guiding her teaching were identified. Also, the parameters of behavior considered “acceptable” in the classroom, so that the students assimilated the social dynamics that they were expected to adopt. Likewise, the assessment approach applied at this educational grade and its implementation in the school day were examined. This analysis not only allowed us to glimpse how teaching and evaluation are articulated in the preschool context, but also offered perspectives to optimize these practices based on a comprehensive education that promotes civic competencies from early childhood.